Islamic Cosmology in Seyyed Hossein Nasr, Zaghloul al-Najjar, and Nidhal Guessoum’s Perspective - Santi, Selvia (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
The development of modern science not only provides an influence in terms of the development of science and technology scientifically but also gets a response from academicians who tried to integrate religion and science. Specifically in this study, the focus of the discourse is directed at the field of cosmology. When interpreted by Islamic thinkers such as Seyyed Hossein Nasr, Zaghloul Al-Najjar, and Nidhal Guessoum, cosmology has added the term to Islamic cosmology. The archeological and genealogical theories of Michel Foucault used in this study attempt to explore further the course of Islamic cosmological discourse developed by the three figures. Archeological and genealogical theories seek the genealogical thinking of those three figures. So, we could find the pattern in every methodology they used and the people who influenced them. The research results show that Islamic cosmology discourse is one of the efforts to Islamize science that is unprecedented in the development of Islamic civilization.